2011
DOI: 10.1007/s11743-011-1295-y
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Fragrances and Fragrance Mixtures Based on Interfacial Solubilization

Abstract: In the present study, the influence of perfumes on the interfacial curvature of microemulsions is investigated. The hydrophilic-lipophilic deviation (HLD) concept was applied to nonionic Winsor I type systems (O/W microemulsions in equilibrium with an oil excess phase) containing a mixture of oils with isopropyl myristate as supporting oil and a variety of liquid solutes as co-oil for which an Equivalent Alkane Carbon Number of the mixture (EACN mix ) was defined. Temperature was used as a formulation variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Recent industry-led presentations at American Oil Chemists Society (AOCS) meetings have introduced experimental and modeling approaches to account for these effects and their impact on surfactant formulation (Dado & Lang, 2021;Ghayour, 2021;Natali & Acosta, 2021). There are now clear connections between phase inversion conditions (HLD = 0) and the performance of formulations in detergency (Phaodee & Sabatini, 2020;Raney et al, 1987;Raney & Benson, 1990;Saito et al, 1985;Thompson, 1994;Tongcumpou et al, 2003); the performance of formulations used to decontaminate oilimpacted soils (Acosta & Quraishi, 2014;Childs et al, 2005;Kibbey & Chen, 2008;Quraishi et al, 2015); the performance of phase inversion methods to produce nanoemulsions (McClements, 2011;Solans et al, 2005); the performance of demulsifiers (Rond on et al, 2006); the formation and breaking of emulsions (Kiran & Acosta, 2015); the formulation with fragrances (Bouton et al, 2009;Tchakalova & Fieber, 2012); the formulation of skin cleaning products (Acosta, 2020), among many others. The connection between the phase inversion conditions and optimal enhanced oil recovery is well known and covered in the classic textbook of Bourrel and Schecter (1988).…”
Section: Practical Implications and Areas For Future Researchmentioning
confidence: 99%
“…Recent industry-led presentations at American Oil Chemists Society (AOCS) meetings have introduced experimental and modeling approaches to account for these effects and their impact on surfactant formulation (Dado & Lang, 2021;Ghayour, 2021;Natali & Acosta, 2021). There are now clear connections between phase inversion conditions (HLD = 0) and the performance of formulations in detergency (Phaodee & Sabatini, 2020;Raney et al, 1987;Raney & Benson, 1990;Saito et al, 1985;Thompson, 1994;Tongcumpou et al, 2003); the performance of formulations used to decontaminate oilimpacted soils (Acosta & Quraishi, 2014;Childs et al, 2005;Kibbey & Chen, 2008;Quraishi et al, 2015); the performance of phase inversion methods to produce nanoemulsions (McClements, 2011;Solans et al, 2005); the performance of demulsifiers (Rond on et al, 2006); the formation and breaking of emulsions (Kiran & Acosta, 2015); the formulation with fragrances (Bouton et al, 2009;Tchakalova & Fieber, 2012); the formulation of skin cleaning products (Acosta, 2020), among many others. The connection between the phase inversion conditions and optimal enhanced oil recovery is well known and covered in the classic textbook of Bourrel and Schecter (1988).…”
Section: Practical Implications and Areas For Future Researchmentioning
confidence: 99%
“…In a previous article a general method for the estimation of surface activity of perfumery ingredients, based on the fluctuation of PIT in a reference system composed of water, surfactant (C 10 E 5 ), and IPM, was introduced . This method is not limited to perfumery ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, we introduced the parameter EACNmix as a measure of the surface activity of the solute with respect to the reference system. We found that solutes with an EACNmix value of more than 5.5 did not express interfacial activity, whereas those with an EACNmix value of less than 5.5 had strong interfacial affinity, leading to a significant swelling of the droplet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, encapsulating the essence in the droplets will provide a more lasting effect due to a controlled release. The high volatility of such small substances in an aqueous phase can make their evaporation fast [374,375].…”
Section: Formulation Of a Functionalized Nanoemulsion For The Adminis...mentioning
confidence: 99%